Dehydrogenases - Angela Canuto, Rosa (IntechOpen, 2012)
The book takes in consideration some dehydrogenases, enzymes with different functions in the cells by using different substrates, such as hydroxysteroid dehydrogenases, aldehyde dehydrogenases, glucose-6-phosphate dehydrogenase, pyruvate dehydrogenase complex, glutamate dehydrogenase, succinate dehydrogenase. They are examined from the following points of view: biochemistry, physiological functions and role in some diseases and in the development of tumours. For these reasons, the book is divided into three sections: 1. Dehydrogenases and cancer 2. Dehydrogenases and some diseases 3. Dehydrogenases and physiological role